Evasão escolar na educação profissional técnica de nível médio: o curso técnico agropecuário no IFGoiano. - Rodrigues, Míriam Antonia Soares Filha (2018)
Philosophical, political and social conceptions of vocational education in Brazil have undergone great transformations throughout history, from the training of free and miserable men to the substitution of slave labor to the scientific and technological formation of young people for the Brazilian market work carried out today by the Federal Institutes of Education, Science and Technology throughout Brazil. One of the main challenges facing this type of training today is the increasing evasion. This paper proposes to examine the social issues related to evasion in the Ceres and Morrinhos campuses of the Federal Institute of Education, Science and Technology Goiano.